Size quantization effects on interfacial electron transfer dynamics in Ru(II)-polypyridyl complex sensitized ZnO QDs - Verma, Sandeep; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry C, 2014)
Quantum-size confinement in semiconductor material offers size based tunability of interband gap energy as well as intraband sublevels. In this work, size quantization of wide bandgap ZnO quantum dots has been explored in the study of interfacial charge separation reaction using a catechol functionalized Ru(II)polypyridyl complex as a photosensitizer molecule. Femtosecond time-resolved transient absorption studies have revealed multiple electron injection events based on discrete conduction band states of ZnO QDs. The electron injection rates have been rationalized for quantum confinement effects owing to different sizes of ZnO QDs. Furthermore, the size dependency of the intrinsic lifetime of electrons injected into discrete energy levels of ZnO QDs has been revealed in charge recombination reaction with the Ru(III)polypyridyl complex cation. The charge recombination dynamics reveals a competing trend of carrier confinement and carrier leak upon reducing particle size. This study shows the optimization of finite size effects in achieving better interfacial charge separation at the dye/semiconductor interface.